Long-Distance Benefits of Marine Reserves: Myth or Reality?. (April 2019) - Manel, Stéphanie; Loiseau, Nicolas; Andrello, Marco; Fietz, Katharina; Goñi, Raquel; Forcada, Aitor; Lenfant, Philippe; Kininmonth, Stuart; Marcos, Concepción; Marques, Virginie; Mallol, Sandra; Pérez-Ruzafa, Angel; et al.
Abstract : Long-distance (>40-km) dispersal from marine reserves is poorly documented; yet, it can provide essential benefits such as seeding fished areas or connecting marine reserves into networks. From a meta-analysis, we suggest that the spatial scale of marine connectivity is underestimated due to the limited geographic extent of sampling designs. We also found that the largest marine reserves (>1000 km 2 ) are the most isolated. These findings have important implications for the assessment of evolutionary, ecological, and socio-economic long-distance benefits of marine reserves. We conclude that existing methods to infer dispersal should consider the up-to-date genomic advances and also expand the spatial scale of sampling designs. Incorporating long-distance connectivity in conservation planning will contribute to increase the benefits of marine reserve networks. Highlights: Marine dispersal distance estimates are limited by the spatial scale of sampling design and therefore biased downwards. Active larval behavior, oceanographic eddies and fronts, tsunamis, marine debris, and translocations are potentially important, but overlooked, dispersal vectors over long distances. The largest marine reserves have the highest potential for massive and long-distance benefits but are the most isolated reserves. Long-distance dispersal has important consequences for the design of marine reserve networks.